The inflow-effect: Trader inflow and bubble formation in asset markets - Michael Kirchler; Caroline Bonn; Jürgen Huber; Michael Razen (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
We investigate the impact of trader and cash inflow on bubble formation in asset markets with a novel design featuring heterogeneous information and a constant fundamental value. Implementing seven treatments we find that (i) only the joint inflow of traders and cash triggers bubbles ("inflow-effect"). (ii) In treatments with trader and cash inflow only in the first half of the market, prices converge to fundamentals towards maturity of the asset. This inflow-effect is very robust as we observe bubbles in almost all of the 24 markets with trader inflow. The analysis of traders' beliefs reveals that (iii) despite fundamentals staying constant, beliefs about fundamentals co-move with upwardly trending prices. Finally, we report a speculative motive only among the optimists in treatments where we observe bubbles.
Keywords: C92; D84; G10; 330; experimental finance; inflow-effect; trader inflow; asset market; bubble; market efficiency